Leadership of School Principles in Improving Teacher's Pedagogical Competence at SMP Smaratungga Ampel - Kabri Kabri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The principal is responsible for the continuity of education and teaching, one of which is in improving gut pedagogic competence. In educational institutions, the principal is the highest leader who plays a role in the development of the school, and education cannot be separated from the existence of the teacher. This research was conducted at SMP Smaratungga, Sampetan Village, Kec. Ampel, Boyolali Regency, Central Java. the research objectives in this thesis are; 1) To describe the principal's efforts in improving the pedagogic competence of teachers. The approach used in this study is a qualitative approach. The type of research used in this research is a case study. Data collection techniques used are interviews, observation and documentation. The analysis used in this study is data condensation, presenting data and drawing conclusions. The results of the research in this thesis are. 1) the principal's efforts to improve the pedagogical competence of teachers at SMP Smaratungga Ampel by using an individual approach. The efforts made include: a ) providing direction, guiding and motivating; b) attend training and participate in MGMP; c) supervision; d) provide understanding; e) hold a meeting; f) planning learning management; g) compiling learning tools; h) provide an understanding of the characteristics; i) mastering student learning theory and learning principles; j) developing curriculum and learning tools; k) develop potential and always direct; l) communicate well.m. assessment and evaluation.n. mid-semester assessment (UTS) first and second semester assessment (UAS) conduct evaluations during the activity process.